Situational ethnicity and identity negotiation: "indifference" as an identity negotiation mechanism. Issue 1 (29th November 2021) - Banerjee, Madhumita; Shukla, Paurav; Ashill, Nicholas J.
Abstract : Purpose: While the literature on migration highlights the reshaping of host and immigrant population in countries, there is a paucity of research in marketing investigating the evolving dynamics for acculturation. The purpose of this study is to further the understanding of the emerging phenomenon of acculturation and identity negotiation. Design/methodology/approach: Three experiments examined situational ethnicity, self-construal and identity negotiation in home and host culture work and social settings. Study 1 and Study 2 were conducted in the United Kingdom (UK), where the host country is the majority population. Study 3 was conducted in the United Arab Emirates (UAE), where the host country is the minority population. Study 4 utilized qualitative interviews in both countries. Findings: Results from all four studies show that ethnic consumers deploy "indifference" as an identity negotiation mechanism when the host society is the majority population (UK) and when the host society has the minority population (UAE). Originality/value: The authors offer new insights into identity negotiation by ethnic consumers when the host society is the majority population as well as the minority population. "Indifference", i.e. preferring to neither fit in nor stand out as an identity negotiation mechanism, is deployed in work and social settings of home and host societies. The authors also advance the existing literature on acculturation by examining whether independent and interdependent self-construal influence identity negotiation.